Merancang peta tiga dimensi secara digital. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Manajemen Pelayanan Kesehatan, Fak. Kedokteran UGM, 2001)
Information dissemination to society will consider successfully, if the information is easy to understand. A map is the best choice to present the information